Investment Decisions in The Era of The COVID 19 Pandemic - Elizabeth Sugiarto Dermawan; M. F. Djeni Indrajati W.; Estralita Trisnawati (International Journal of Application on Economics and Business, 2023)
The purpose of this study was to obtain empirical evidence regarding investment decisions from students of the Faculty of Economics and Business (FEB) in 4 Universities in Jakarta during the COVID-19 pandemic era which was in a condition full of uncertainty. The test of this research is the Spearman's rho correlation test through SPSS version 20 because the data is not normal. The data processed by 160 respondents were distributed via google form during July – September 2020. Referring to the theory of investor behavior, the results of this study are expected to describe investment decisions in the era of the COVID-19 pandemic. The results of the Spearman's rho correlation test that are significant with regard to investment decisions are investment risk, investment returns, and general information, while financial information is not significantly related to investment decisions. This shows the behavior of investors not to make investment decisions using financial information that is considered as past data considering that future conditions will be much different from the past. The implications of this research are to motivate investors to keep investing in the era of the COVID-19 pandemic in order to stimulate.